Kinetic percolation - Heinson, W. R.; Chakrabarti, Amitabha; Sorensen, Christopher M. (My University, 2017)
We demonstrate that kinetic aggregation forms superaggregates that have structures identical to static percolation aggregates, and these superaggregates appear as a separate phase in the size distribution. Diffusion limited cluster-cluster aggregation (DLCA) simulations were performed to yield fractal aggregates with a fractal dimension of 1.8 and superaggregates with a fractal dimension of D = 2.5 composed of these DLCA supermonomers. When properly normalized to account for the DLCA fractal nature of their supermonomers, these superaggregates have the exact same monomer packing fraction, scaling law prefactor, and scaling law exponent (the fractal dimension) as percolation aggregates; these are necessary and sufficient conditions for same structure. The size distribution remains monomodal until these superaggregates form to alter the distribution. Thus the static percolation and the kinetic descriptions of gelation are now unified.
Citation: Heinson, W. R., Chakrabarti, A., & Sorensen, C. M. (2017). Kinetic percolation. Physical Review E, 95(5), 6. doi:10.1103/PhysRevE.95.052109
Keywords: Laminar Diffusion Flames; Fractal Dimension; Gelation; Gels; Aggregation; Physics